2016
DOI: 10.1097/aln.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Practice Guidelines for Obstetric Anesthesia

Abstract: The American Society of Anesthesiologists Committee on Standards and Practice Parameters and the Task Force on Obstetric Anesthesia and the Society for Obstetric Anesthesia and Perinatology present an updated report of the Practice Guidelines for Obstetric Anesthesia. Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(71 citation statements)
references
References 209 publications
(220 reference statements)
0
62
0
9
Order By: Relevance
“…Nausea and vomiting are the main adverse effects of tramadol. Antiemetics (either pharmacological or acupressure) should be offered to reduce the incidence of nausea and vomiting 24. Respiratory depression evaluated by ventilator use was not observed in this study.…”
Section: Discussionmentioning
confidence: 62%
“…Nausea and vomiting are the main adverse effects of tramadol. Antiemetics (either pharmacological or acupressure) should be offered to reduce the incidence of nausea and vomiting 24. Respiratory depression evaluated by ventilator use was not observed in this study.…”
Section: Discussionmentioning
confidence: 62%
“…The significantly longer catheter dwell time and insertion at an earlier cervical dilatation, were not associated with extension failure. This result is important, given suggestions by experts and international guidelines, that epidurals be inserted early in labor, for obese women 9, 25, 26…”
Section: Discussionmentioning
confidence: 99%
“…These cohort studies have identified a significantly higher rate of cesarean section, general anesthesia and problems or failure of neuraxial anesthesia in this group 28, 29. International maternity care guidelines make recommendations regarding the care of pregnant women with a BMI > 40 kg/m 2 , but do not differentiate between levels of BMI greater than 40 kg/m 2 25, 26, 30. Pregnant women with a BMI > 50 kg/m 2 may present specific management difficulties, necessitating different ‘ideal’ obstetric and anesthetic management.…”
Section: Discussionmentioning
confidence: 99%
“…Even the very recent (2016) guidelines for obstetrical anesthesia from the American Society of Anesthesiologists (ASA)14 avoid suggesting a clear guidance and just state: “A specific platelet count predictive of neuraxial anesthetic complications has not been determined.” In general, a platelet count of ≥50×10 9 /L is recommended for safe delivery 4. Therefore, in most cases, general anesthesia is preferred, due to severe thrombocytopenia and considering the risk of possible spinal or epidural hematoma 1416…”
Section: Discussionmentioning
confidence: 99%